Transformation of Banking Industry by Information Technology (IT) - WÓJCIK-CZERNIAWSKA Agnieszka (Communications of International Proceedings, 2022)
Information technology's influence on all elements of human existence and business is so obvious that it doesn't need to be stated. Information technology's relevance in the banking business cannot be emphasized. Information technologies (ITs) have grown in the banking industry over the past few years. The banking sector has invested a considerable sum of money in utilizing innovative technologies to enhance banking services. The growing digitization has altered the traditional business models used by banks in the financial services sector. The goal of this paper is to transform the banking industry by the information technology. The secondary research methods have been used in this article and data has been gathered through the internet, libraries, archives, schools and organizational reports. Online data is data that is gathered via the internet. In the banking business, information technology (IT) is swiftly showing to be a vital and effective platform for enhancing expansion, prosperity, creativity, and competition. Information technology enhances the financial sector in 3 stages, according to the research results: it cuts customers and staff time, lowers costs, and simplifies transaction processing. Fewer investment deals and declining profits for banks could signal layoffs. However, banks are well positioned to hang onto employees until they see how H2 shapes up. Shifting from banking services to a digital world is only one aspect of digital transformation. It represents a significant shift in the way banks learn from, communicate with, and serve their clients.
Keywords: digital strategy; digital transformation; digital banking; Information technology